Ambient ozone and mortality from respiratory diseases: A nationwide analysis in China - Weiling Tang; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Zhulin Hou; Jianxiong Hu; Guanhao He; Lifeng Lin; Yanfang Guo; et al. (Global Transitions)
Background: Although the health impacts of ambient ozone (O3) have been widely assessed, studies simultaneously investigating the acute and chronic effects of O3 on mortality from respiratory diseases (RESP) are scarce. Methods: We extracted personal information of all recorded deaths from RESP throughout 2013–2018 in six provinces in China. The daily, seasonal, and annual mean air pollutant concentrations at the township/subdistrict level were estimated by a random forest model. The acute association between the maximum daily average 8h ozone (MDA8 O3) and RESP mortality was examined by a time-stratified case-crossover study design, and the chronic association was estimated by a difference-in-differences (DID) analysis approach. We also calculated the attributable fraction (AF) of RESP mortality attributable to MDA8 O3. Results: There were 1,034,226 RESP deaths included in this study. The excess risks (ERs) of overall RESP mortality for each 10 μg/m3 increase in short-term (lag03 days) and long-term (one-year average) exposure to MDA8 O3 were 0.38 % (95%CI: 0.26 %, 0.50 %) and 4.37 % (3.91 %, 4.84 %), respectively. The AFs of overall RESP mortality ascribed to short- and long-term MDA8 O3 exposures were 3.00 % (2.03 %, 3.95 %) and 29.45 % (26.86 %, 31.95 %), respectively. The average annual number of RESP deaths attributable to short-term MDA8 O3 exposure was 30,790 and 302,254 were attributable to long-term MDA8 O3 exposure across China during 2013–2018. Conclusion: Both short- and long-term exposure to ambient MDA8 O3 were positively associated with RESP mortality, and long-term exposure to MDA8 O3 may lead to a greater RESP mortality burden than short-term exposure to MDA8 O3.